Pengembangan Basis Data Sistem Informasi Manajemen Rumah Sakit Berbasis Linguistic-based Schema Matching - Adhistya Erna Permanasari; Hayu Pradnya Satyaprabha; Addin Suwastono; Guntari Titik Mulyani (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
Prof. Soeparwi veterinary hospital is one of the medical institutions focused on providing medical services for animals. In its daily operations, the flow of informations among various departments has yet to be supported by management information systems (MIS) which enables efficiency of business process and a better management of the data. Previous researches have been conducted to develop MIS, which resulted in three independent MIS for managing registration, medical records, and patient bills. Each MIS is using their own database to store the data, thus causing duplicates of information and inconsistencies, and also increasing complexity in accessing the data. The goal of this research is to re-design the said database into a single database that will be used by various MIS. Three independent databases are merged by applying a technique that uses linguistic information as the basis for the matching–called linguistic-based schema matching. This method’s accuracy is evaluated by calculating precision, recall, and F-measure–which we obtained scores of above 50% for all three indicators. Requirement analysis is performed to further develop the database for supporting further needs of the hospital. The new database system is tested using black-box technique under few test cases to see if its functionality corresponds with the specifications defined. Result of this test proves that the new database could handle valid, invalid, and redundant inputs as expected by a score of 100% success rate.